FLIP-mediated autophagy regulation in cell death control - Lee, Jong-Soo (2009)
Autophagy is an active homeostatic degradation process for the removal or turnover of cytoplasmic components wherein the LC3 ubiquitin-like protein undergoes an Atg7 E1-like enzyme/Atg3 E2-like enzyme-mediated conjugation process to induce autophagosome biogenesis1–4. Besides its cytoprotecive role, autophagy acts on cell death when it is abnormally upregulated. Thus, the autophagy pathway requires tight regulation to ensure that this degradative process is well balanced. Two death effector domains (DED1/2) containing cellular FLICE-like inhibitor protein (cFLIP) and viral FLIP (vFLIP) of Kaposi’s sarcoma-associated herpesvirus (KSHV), Herpesvirus saimiri (HVS), and Molluscum contagiosum virus (MCV) protect cells from apoptosis mediated by death receptors5,6. Here, we report that cellular and viral FLIPs suppress autophagy by preventing Atg3 from binding and processing LC3. Consequently, FLIP expression effectively represses cell death with autophagy, as induced by rapamycin, an mTor inhibitor and an effective anti-tumour drug against KSHV-induced Kaposi’s sarcoma (KS) and primary effusion lymphoma (PEL)7,8. Remarkably, either a DED1 α2-helix ten amino-acid (α2) peptide or a DED2 α4-helix twelve amino-acid (α4) peptide of FLIP is individually sufficient for binding FLIP itself and Atg3, with the peptide interactions effectively suppressing Atg3–FLIP interaction without affecting Atg3-LC3 interaction, resulting in robust cell death with autophagy. Our study thus identifies a checkpoint of the autophagy pathway where cellular and viral FLIPs limit the Atg3-mediated step of LC3 conjugation to regulate autophagosome biogenesis. Furthermore, the FLIP-derived short peptides induce growth suppression and cell death with autophagy, representing biologically active molecules for potential anti-cancer therapies.